An interesting case of Cruveilhier-Baumgarten disease: Persistent left umbilical vein in a 50 year old man - Thukral, Anubhav; Srivastava, Vaibhav; Dwivedi, Amit Nandan Dhar; Mishra, Manish; Tripathi, Kamlaker (Asian Journal of Medical Sciences, 2011)
A middle aged man of 50 years presented with features of portal hypertension without any features of liver decompensation or cirrhosis, found to have abnormal flow pattern in peri-umbilical vein, confirmed by Doppler to have a patent left umbilical vein. This represents a very treatable cause of portal hypertension as ligation of vein may result in complete reversal of disease process. The case also outlines importance of routine general examination like of seeing the direction of flow in periumbilical veins even in obvious cases of portal hypertension that helped us in detection of this case. Key Words: Portal hypertension; Periumbilical vein DOI: 10.3126/ajms.v2i1.3780 Asian Journal of Medical Sciences 2 (2011) 63-64